Menyuarakan yang Sunyi: Narasi Amnon-Tamar dalam 2 Samuel 13:1-22 sebagai Dasar Pemulihan Trauma bagi Penyintas di Indonesia - Ragil Kristiawan; Pujiati Pujiati (Jurnal Pistis: Teologi dan Praktika, 2026)
The background of this research is the high incidence of sexual violence in Indonesia, which leaves complex trauma, while healing approaches often neglect cultural-religious dimensions. The narrative of Amnon and Tamar (2 Sam. 13:1-22) depicts trauma dynamics and systemic support failures. This research aims to reflect on this narrative to formulate contextual trauma healing principles for survivors of sexual abuse in Indonesia. Using qualitative textual-narrative analysis and contextual theological reflection, the discussion identifies three main principles neglected in the response to Tamar: creating safe space (safety), acknowledgment and mourning (remembrance and mourning), and reconnection through restorative justice (reconnection through restorative justice). These principles are relevant for addressing the culture of silence, stigma, and authority failures in Indonesia, while demanding a transformative role for faith communities as safe spaces, long-term companions, and agents of justice. This research concludes that this biblical narrative provides a strong reflective basis for building a holistic and contextual trauma-healing model in Indonesia.